Detection and Recognition of File Masquerading for E-mail and Data Security - Dhanalakshmi, R.; Chellappan, C. (Recent Trends in Network Security and Applications, 2010)
Due to the tremendous improvement of internet technology and increasing importance of privacy, security, and wise use of computational resources, the corresponding technologies are increasingly being faced with the problem of file type detection. Digital forensics deals with an investigation of digital evidence to enable investigators to detect the facts for the offences. In digital forensics, there are numerous file formats in use and criminals have started using either non-standard file formats or change extensions of files while storing or transmitting them over a network. This makes recovering data out of these files difficult. This also poses a very severe problem for the unauthorized users to send malicious data across the network and it is essential to tackle this e-crime which may harm the entire organization and network . File type detection has the most usage and importance in the proper functionality of operating systems, firewalls, intrusion detection systems, anti viruses, filters, steganalysis and computer forensics. Certain organizations may ban specific file formats via their intranet or E-mail services and the technique to change file extension in sending across has to be severely monitored. Identifying the type of file format of a digital object will be a crucial function on ingest to a digital repository thereby attaining improved security and fraud prevention .This paper focuses on identifying the true file type , detect the presence of embedded data types to improve analysis efficiency in Digital forensic .